1 Answer | Add Yours
You need to convert the summation of logarithms into the logarithm of product, such that:
`log_3 2 + log_3 a = log_3 (2a)`
Since `log_3 2 + log_3 a = 1` , you need to replace `log_3 (2a)` for `log_3 2 + log_3 a,` such that:
`log_3 (2a) = 1 => 2a = 3^1 => a = 3/2`
Since a is the argument of logarithms, it needs to be positive, hence, `a = 3/2 ` is valid.
Hence, evaluating the value of a, under the given conditions, yields `a = 3/2.`
We’ve answered 319,197 questions. We can answer yours, too.Ask a question